2019
DOI: 10.1007/s11154-019-09487-y
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of radiofrequency ablation in autonomous functioning thyroid nodules. A systematic review and meta-analysis

Abstract: Whether thermal ablation is effective to treat toxic thyroid nodules (TTN) is still unknown. Aim of this review was to achieve more robust evidence on the efficacy of radiofrequency ablation (RFA) in treating TTN in terms of TSH normalization, thyroid scintiscan, and volume reduction rate (VRR). A comprehensive literature search of PubMed/Medline and Scopus was performed in November 2018 to retrieve published studies. Original papers reporting TTN treated by RFA and later followed-up were eligible. Excluded we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 31 publications
2
42
0
2
Order By: Relevance
“…The trial was powered for volume reduction superiority of RFA compared with LA. Based on published data, we expected at least a 10% difference in nodule volume reduction between the RFA and the LA group (15). We calculated that a sample size of 30 participants per group was needed to have a power of about 90%, with a type I error rate of 5%, by estimating that the standard deviation (SD) would be as large as the expected difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trial was powered for volume reduction superiority of RFA compared with LA. Based on published data, we expected at least a 10% difference in nodule volume reduction between the RFA and the LA group (15). We calculated that a sample size of 30 participants per group was needed to have a power of about 90%, with a type I error rate of 5%, by estimating that the standard deviation (SD) would be as large as the expected difference.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analysis and retrospective studies reported contradictory results regarding RFA and LA efficacy for treating BTNs (11,(13)(14)(15)(16). However, there are no direct prospective studies that compare the two techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Image-guided thyroid ablation (I-GTA), such as radiofrequency (RF) and laser ablation, is mainly used to treat benign nonfunctioning thyroid nodules that show progressive growth over time, become symptomatic, or show cosmetic Twelve-Month Volume Reduction Ratio Predicts Regrowth and Time to Regrowth in Thyroid Nodules Submitted to Laser Ablation: A 5-Year Follow-Up Retrospective Study concerns (1,2). In the last decade, several studies confirmed that laser ablation and RF are effective for cystic and hot thyroid nodules and are considered safe and cost-effective (3)(4)(5)(6). Several studies demonstrated a significant benefit in the volume reduction ratio (VRR), usually by 50.0-80.0% over a follow-up period of up to 5 years (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the use of PEI in solid thyroid nodules is contraindicated, unless it is the only available treatment [20][21][22][23][24]. According to the studies, PEI in nonfunctioning nodules had been associated with about 50% of nodular volume reduction [25][26][27]. Consistent with previous studies, in our research, the PEI was associated with the mean volume reduction of 37.4%, 55.6%, and 72.2%, at the baseline of the study, 1, 3 and six months after the intervention, respectively.…”
Section: Discussionmentioning
confidence: 99%